The First Contact of Human Dendritic Cells With Trypanosoma cruzi Reveals Response to Virus as an Unexplored Central Pathway - Gil-Jaramillo, Natalia; Rocha, Amanda Pereira; Raiol, Tainá; Motta, Flávia Nader; Favali, Cecília; Brigido, Marcelo M.; Bastos, Izabela M. D.; Santana, Jaime M. (Frontiers in Immunology, 2021)
Chagas disease is a debilitating and neglected disease caused by the protozoan Trypanosoma cruzi. Soon after infection, interactions among T. cruzi and host innate immunity cells can drive/contribute to disease outcome. Dendritic cells (DCs), present in all tissues, are one of the first immune cells to interact with Trypanosoma cruzi metacyclic trypomastigotes. Elucidating the immunological events triggered immediately after parasite-human DCs encounter may aid in understanding the role of DCs in the establishment of infection and in the course of the disease. Therefore, we performed a transcriptomic analysis of a 12 h interaction between T. cruzi and MoDCs (monocyte-derived DCs) from three human donors. Enrichment analyses of the 468 differentially expressed genes (DEGs) revealed viral infection response as the most regulated pathway. Additionally, exogenous antigen processing and presentation through MHC-I, chemokine signaling, lymphocyte co-stimulation, metallothioneins, and inflammasome activation were found up-regulated. Notable, we were able to identify the increased gene expression of alternative inflammasome sensors such as AIM2, IFI16, and RIG-I for the first time in a T. cruzi infection. Both transcript and protein expression levels suggest proinflammatory cytokine production during early T. cruzi-DCs contact. Our transcriptome data unveil antiviral pathways as an unexplored process during T. cruzi-DC initial interaction, disclosing a new panorama for the study of Chagas disease outcomes.